Frozen ground temperature records (2022-2024) for rocky slopes in the Argentinian Andes at ca. 33.62°S (Portillo Argentino, Tunuyán, Mendoza) - Tapia Baldis, Carla Cintia
Ground temperature (°C) was collected in the frozen rocky outcrops in the Portillo valley, from 2022 to 2024. Portillo valley (Tunuyán, Mendoza) is placed in the Argentinian Central Andes at >4000 m a.s.l. (-33.621889°S; -69.607833°W). The purpose of the data set is to explore the freezing/thawing conditions in the study site (7 observation sites), as well as evaluate the permafrost presence. The iButtons DS1922L (Maxim Integrated) took 6 measurements per day, at 00:00, 04:00, 08:00, 12:00, 16:00 and 20:00 hours (GMT-3), from 27/01/2022 to 25/03/2024. Fil: Tapia Baldis, Carla Cintia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina